'Doing' digital transformation: theorising the practitioner voice. (15th December 2022) - McCarthy, Patrick; Sammon, David; Alhassan, Ibrahim
ABSTRACT: The objective of this theory-building research is to explore the defining characteristics of 'doing' Digital Transformation (DT) and present a holistic account of the practitioner practices that characterise 'doing' DT. For the purposes of this research 'doing' DT is defined as leveraging digital technologies to significantly alter an organisational design in order to enhance customer engagement. To fulfil this objective, we select 16 key informants (digital transformation leaders) based on their organisational perspective (Business or IT) and role (Strategic or Operational), which facilitates hearing 4 types of practitioner voices. Following an inductive open coding approach, 348 excerpts were coded, leading to the emergence of 95 concepts, which were further grouped into 14 categories. In this paper, we focus our write-up on the six most frequently occurring categories that are shaped by all four key informant groups (practitioner voices). This paper is unique in providing a holistic categorisation of the defining characteristics of 'doing' DT, while also providing 24 'Practitioner Priorities'. These 'Practitioner Priorities' sharpens the focus of academia and practice, highlighting the 'role of people', 'role of data' and 'role of technology' when 'doing' DT.